Microbiological assessment of spaghetti meal from a selected franchised food establishment in Iloilo City - Palma, Honey Hyacinth Baltazar (2007.)
The study assessed the safety quality of spaghetti meal from a franchised food establishment.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Spaghetti; Safety quality